Ribavirin Stimulates the Immune Response of Atlantic Salmon - Spencer-Ossa, E; Sandino-Garcia, A; Imarai-Bahamonde, C; Rivas-Aravena, A; Valenzuela-Montenegro, B (Elsevier, 2015)
Ribavirin is a synthetic nucleotide analog capable of inhibiting or even preventing some viral infections in mammals and also in fish. It has been seen by others that ribavirin by itself is able to stimulate the immune system of mammals, causing a differentiation of T-cells to T helper 1 cells (Th)-1. In this work, we evaluated the immune effect of ribavirin in vitro on kidney cells from Atlantic salmon and in vivo by oral administration of ribavirin to Atlantic salmon. For this purpose, the transcripts of immune molecules Tbet, GATA3, CD8, CD4, IFNα, IFNγ, IL-4/13, IL-10, IL-12, IL-15 and TGF-B were quantified. The results show that ribavirin administered orally in food to Atlantic salmon increased IFNγ and CD4 transcripts in the in vivo assays and, in addition, increased IL-12, IL-15 and CD8 in the in vitro analyses, indicating that the treatment stimulates a Th1 type response in salmon. © 2015 Elsevier B.V.